Migratory containment in pandemic: Territorial configuration of detentions and deportations in Mexico's borders - Castillo Ramírez, Guillermo (2024)
Irregularized populations of the North of Central America bound for the United States and in transit through Mexico have experienced state dynamics of migratory containment. This article argues that, through the consultation of official sources and during the pandemic (2020-2021), spatial changes were observed in detentions and deportations of Central American migrants by the Mexican government. This was related with two processes: sociodemographic changes of said migrations and certain state measures (closure and border securitization). It is argued that the territorial configuration of detentions and deportations was not homogeneous and was part of the migratory containment, presenting spatial concentrations of detentions and deportations on the southern and northern borders of Mexico. The contribution of the work is, in the context of the Covid19 emergency, to address the sociodemographic and territorial transformations of detentions and deportations as part of political processes of Mexican migration containment and in relation to irregularized migrations.